Bibb County, Alabama : the first hundred years, 1818-1918 - Ellison, Rhoda Coleman, 1904-2005 (University of Alabama Press, 1999)
This model county history chronicles one hundred years in the life of a representative Deep South county. The history of Bibb County between 1818 and 1918 is in many ways representative of the experience of central Alabama during that period. Bibb County shares physical characteristics with the areas both to its north and to its south. In its northern section is a mineral district and in its southern valleys fertile farming country; therefore, its citizens have sometimes allied themselves with the hill counties and sometimes with their Black Belt neighbors. Both sections of the county develop. -- Provided by publisher.